Beyond the border: narrating the journey of the Palestinian refugees in Jordan - Natsheh, Abdullah (My University, 2022)
This thesis intends to narrate the journey of Palestinian refugees, choosing Jordan as the study area. It will highlight the stages of the Palestinian journey from exile, displacement, the legal right to return to their homeland, and their lives as refugees in a different country. With a focus on analyzing the tangible and intangible aspects of a Palestinian refugee camp in Jordan in light of its state of permanent temporariness; as it acts as a significant factor in the lives of the Palestinian refugees and their journey. The temporary role of the refugee camps has caused an issue for the lack of certainty on how long this temporary state might persist, often it lasts longer than anticipated, and in the Palestinian case it has gone on for 74 years, which had negative impacts on the built environment of the refugee camps and the sense of identity. The outcome of this thesis focuses on preserving the Palestinian journey and conserving a nation’s memory while raising awareness about the lives of millions of unfortunate individuals who were forced to flee their homeland to survive. It is also a personal notion of being a link between the author and his ancestral roots, being a Jordanian citizen from Palestinian roots.